Uji Efektivitas Antidepresan Kulit Bawang Merah (Allium Cepa L.) Terhadap Mencit Putih Jantan (Mus Musculus) - Saputri, Gusti Ayu Rai; Primadiamanti, Annisa; Andrianti, Windi (Peneliti.net, 2024)
Depression can be caused by biological factors, psychological factors and social factors. This study aims to determine the effectiveness of Red Onion Peel Extract (Allium cepa L.)as an antidepressant in mice.The method used for the antidepressant test is TST (Tail Suspension Test) to make mice stress and FST (Forced Swim Test) to see immobility time.The test animals used male mice divided into five treatment groups given orally.The results showed that K+ (Amitriptiline25mg), K-(Na-cmc05%), KU1 (200mg/kgBw), KU2 (250mg/kgBw) and KU3 (300mg/kgBw) had an antidepressant effect by showing the occurrence of immobility time. The result of One Way ANOVA immobility time test is a value of 0.003 which states that shallot skin can affect the immobility time of mice. It can be concluded Giving variant doses of shallot skin extract (Allium cepa L.) gives the effect of immobility time on male white mice (Mus musculus) with the most effective dose as an antidepressant is a dose of 300 mg / kgBB..